Efecto comparativo de la melaza de caña y harina de yuca en la utilización de úrea en la alimentación de rumiantes. (1978)
An experiment was conducted to evaluate the effect of molasses and cassava meal (Ma,uihot esculenta) as energy sources in fattening steers fed diets supplemented with urea and cotton seed meal, as protein sources, at levels of 100 and 300 gms/head/ day, respectively. In treatment 1, 1,0 kg of molasses was given per head daily. In treatment II, 0,5 kg of molasses was replaced by 0.375 kg of cassava meal. And in treatment III, all the amount of molasses was replaced by 0,750 kg of cassava meal. Corn silage was given as roughage. Salt and minerals were given ad libiturn. Average daily gains were 0.766, 0.809 and 0.859 kg for treatments I, II and III, respectively. Differences were not significant. However, the average daily gain was 12.1% greater when 1.0 kg of molasses was replaced by cassava meal on a dry matter basis. If seemed that starch increased urea utilization presumably by encouraging microbial synthesis. The replacement of molasses for cassava meal would be economically feasible, when the cost of those ingredients on a dry matter basis be equal.